Motives of Non-American Firms Investing in the United States - Ajami, Riad A.; Ricks, David A. (Journal of International Business Studies, 1981)
Non-American firms have recently begun investing larger sums of money in the U.S. Such increased activity has created a great deal of interest and concern. The growth in foreign direct investment and findings of a mailed questionnaire will be reviewed in this article. Factor analysis was utilized to help isolate the salient motives for these investment activities. Although the size of the U.S. market and the attractiveness of a new market or the desire to preserve the existing U.S. market were the most frequently cited reasons for new investment in the U.S., factor analysis reveals that these reasons merely reinforce the primary motive: namely, the desire to benefit from a higher level of U.S. technology and innovation.